Proposal and analysis of a poly-generation process for coal gasification and ironmaking. (June 2022) - Yang, Yiru; Wang, Zhe; Guo, Lei; Wen, Xiaochun; Guo, Zhancheng
Highlights: A novel poly-generation process for coal gasification and ironmaking was proposed. The thermodynamics model predicated the ideal products for variant cases of GRCP. The exergy efficiency of GRCP is slightly lower than that of CGP-GSP as 83.6%. Storage of chemical exergy in DRI was an essential energy-saving reason. Abstract: The novel gasification-reduction coupling process (GRCP) was proposed to obtain higher coal gas/hot metal poly-generation system efficiency. The hematite particles replaced previous moderators (H2 O/CO2 ) in the entrained-flow gasifiers, and direct reduced iron (DRI) can be obtained simultaneously. In this study, the thermodynamic model was established to predicate material streams in GRCP. Numerous cases with different material ratios were also examined to investigate the relevant effects, such as effective gas ratio ([CO] + [H2 ]), metallization ratio (Fe wt.%), and reduction degree (R). To further quantify energy streams, the exergetic analysis was also conducted according to different definitions. The results indicated that both chemical and physical exergy of high temperature reducing gas transferred into DRIs through the coupling process. Therefore, a significant decrease was observed in cold gas efficiency (72.7%). The exergetic evaluation also shows that GRCP still kept a high-level (83.6%) based on all substances. Since the chemical exergy of DRI was stable exergy storage during the subsequent utilization, higher system efficiency can be expected in the further development of GRCP.